2003
DOI: 10.1007/s11612-003-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Auswirkungen von Downsizing-Maßnahmen auf das organisationale Commitment der verbleibenden Mitarbeiter: Ein Vorher-Nachher-Vergleich

Abstract: Auswirkungen von Downsizing-Maßnahmen auf das organisationale Commitment der verbleibenden Mitarbeiter: Ein Vorher-Nachher-VergleichIn einem mittelständischen Telekommunikationsunternehmen wurden die Auswirkungen betrieblicher Umstrukturierungen, die mit Personalabbau einhergingen ("Downsizing"), auf das organisationale Commitment, die Mitarbeiterzufriedenheit und -motivation der verbleibenden Mitarbeiter ("Survivors") untersucht. Die Erhebung des organisationalen Commitments basierte auf einem im Rahmen des D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…For example, Allen, Freeman, Russell, Reizenstein, and Rentz (2001) found that reductions in downsizing survivors' feelings of employment security were associated with lowered organizational commitment (β = .31) and heightened turnover intentions (β = −.18), with the decrease in organizational commitment persisting 1 year after the downsizing. Krause, Stadil, and Bunke (2003) reported similar findings from a study with employees who simply witnessed layoffs in another organization rather than experiencing layoffs within their own organization.…”
Section: Careers and The Psychological Contractsupporting
confidence: 53%
“…For example, Allen, Freeman, Russell, Reizenstein, and Rentz (2001) found that reductions in downsizing survivors' feelings of employment security were associated with lowered organizational commitment (β = .31) and heightened turnover intentions (β = −.18), with the decrease in organizational commitment persisting 1 year after the downsizing. Krause, Stadil, and Bunke (2003) reported similar findings from a study with employees who simply witnessed layoffs in another organization rather than experiencing layoffs within their own organization.…”
Section: Careers and The Psychological Contractsupporting
confidence: 53%